Waterfall-ADDIE model: an integration of software development model and instructional systems design in developing a digital video learning application - Wan Nor Ashiqin Wan Ali; Wan Ahmad Jaafar Wan Yahaya (Penerbit Universiti Kebangsaan Malaysia, 2023)
To date, researchers are still debating the poor instructional design for certain developed learning applications or courseware in supporting the flexibility to the student. The instructional design is vital in ensuring that learners obtain effective and meaningful to them for a better subject understanding. However, ignoring the functionality and bugs issues in a courseware development should not be practiced. The courseware developer should acknowledge the importance of instructional design and system development model to meet the user and system requirements. Given the resemblances between software development and instructional design phases, researchers could integrate certain importance techniques in software development model’s phases into the ISD model to enhance the design solutions as well as the application technical parts. This paper highlights the integration of Waterfall model as the software development model with ADDIE model which is one of the established ISD models. The integration of Waterfall-ADDIE model was adopted to develop the digital video learning application for university students. A system testing and user acceptance testing were conducted to validate the courseware can meet the system and user requirements. This paper demonstrates all the phases involved in Waterfall model and ADDIE model are interrelated and practically being integrated to propose high-quality development of instructional design learning material.